PHOTOMETRIC STUDY OF TY CRA - Shevchenko, V. S.; Vitrichenko, E. A.; The. D. de Winter, P. S. (Одеські астрономічні публікації, 2017)
The UBVRI photometric data of TY CrA have been compiled mostly unpublished. The new period and epoch have been derived: Min I = JD 2442954.301+2.888782E. The errors are about 2 units in the last digit. At the first time the V light curve have been solved. The elements are: r1 = r2 = 0.13, L1 = 0.92, i = 81.7°. The light curve has no phase effect. No color variation have been seen. There is some depression near phase 0.5. If it is real, the relative surface brightness evaluation leads to conclusion that the secondary may be a F0 star with 2 M⊙.